The Effect of Electroslag Remelting on the Cleanliness of CrNiMoWMnV Ultrahigh-Strength Steels - Ali, Mohammed; Porter, David; Kömi, Jukka; Heikkinen, Eetu-Pekka; Eissa, Mamdouh; El Faramawy, Hoda; Mattar, Taha (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The effect of electroslag remelting (ESR) using CaF2:Al2O3:CaO (70:15:15) synthetic slag on the cleanliness of ultrahigh-strength steels (UHSS) has been investigated. Three grades of UHSS were designed and produced via an induction furnace melting and then refined using ESR. The produced ingots were hot forged with start forging temperature 1100 oC and end forging temperature 950 oC then air cooled. Investigation of the non-metallic inclusions in produced steels has been carried out using field emission scanning electron microscopy and laser scanning confocal microscopy.  Thermodynamic calculations for the expected NMIs formed in the investigated steels with and without ESR have been performed using FactSage 7.2 software while HSC Chemistry version 9.6.1 has been used to calculate the standard Gibbs free energy (DG0). Depending on the steel composition and as a result of ESR; the total impurity levels (TIL% = O% + N% + S%) and NMI contents decreased by as much as 46% and 62% respectively. The NMIs were classified into four major classes: oxides, sulphides, nitrides and complex multiphase inclusions. ESR brings about large changes in the area percentages, number densities, maximum equivalent circle diameters and the chemical composition of the various inclusions. Most MnS inclusions were removed although some were re-precipitated on oxide or nitrides inclusions leading to multiphase inclusions with an oxide or nitride core surrounded by sulphide, e.g. (MnS.Al2O3) and (MnS. TiN). Also, some sulphides are modified by Ca, forming (CaMn)S and CaS.Al2O3. Some nitrides like TiN and (TiV)N are nucleated and precipitated during the solidification phase. Al2O3 inclusions were formed as a result of the addition of Al as a deoxidant to the ESR slag to prevent penetration of oxygen to the molten steel.